Continuous idea contribution in open innovation communities: The role of verbal persuasion from peers - Zhang, Jiacheng; Qi, Guijie; Song, Chunlin; Chen, Jiali (Frontiers in Psychology, 2022)
Motivating continuous idea contributions from members is especially challenging for open innovation communities (OIC). Scholars have thus explored a range of incentives, among which peer feedback has received much attention. However, existing research on peer feedback tends to focus on the structural features, ignoring the richness of the text. To fill this research gap, this study investigates the influence of feedback language use from peers, including emotional support and constructive feedback, on individuals’ continuous idea contributions, based on the creative self-efficacy theory. The results show that emotional support, especially emotional approval, positively affects members’ continuous contributions, and that the effect is stronger when the provider is of a higher status. However, individualized consideration does not seem to work. In addition, in terms of the effect of constructive feedback, we also find support from cognitive stimulation, while intellectual stimulation exerts an effect only when the provider’s status is high. Overall, these findings extend the current research on peer feedback and offer practical guidelines to the open innovation community.